Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Kualitas Kinerja Karyawan di PT. PLN(Persero) UP3 Kota Parepare - Albad, Ghina Alvina Putri; Ramadani, Sahrul; Ilahi, Andi Alfianto Anugrah; Dinsar, Arfandy (Jurnal Ilmiah Multidisiplin Amsir, 2024)
The study analyzes the human resource development strategy at PT. PLN (Persero) UP3 Kota Parepare and its impact on employee performance. Using a descriptive qualitative method, the study found that PT. PLN (Persero) UP3 Kota Parepare successfully implemented effective training such as On the Job Training (OJT) and Off the Job Training (Off-JT), which enhanced employees' skills and knowledge. This strategy improved productivity, efficiency, adaptability to changes, employee satisfaction, retention, and a positive work culture. In conclusion, the human resource development strategy at PT. PLN (Persero) UP3 Kota Parepare has improved employee performance and had a positive impact on the company. This strategy must continue to be implemented and adjusted to meet labor market needs to ensure optimal employee performance